Using virtual and physical learning spaces to develop a successful mathematical learning community, both for on-site and distance provision - Huntley, Belinda; Middleton, Andrew; Waldock, Jeff (MSOR Connections, 2019)
This paper considers learning space and its relationship to student belonging and becoming. Student engagement, satisfaction and academic success are outcomes of a supportive learning community which can flourish in a culture of expectation and behaviour created by providing suitable support structures and by considering the effective use of physical and virtual learning spaces. We describe our innovative use of discipline-specific virtual and physical spaces to develop successful mathematical learning communities, in both a UK university where activities are principally face-to-face, and at a South African university where they are mainly virtual. By comparing our practices and spaces, we explore the ‘equivalence of place’ and the roles of academic staff in fostering the development of professional learner identities through each context. Based on evidence from our respective practices, we make recommendations for designing new learning spaces and for making effective use of existing learning spaces. Although this study focuses on mathematics, many of these suggestions can benefit all disciplines.